Minimizing pre-shock chest compression pauses in a cardiopulmonary resuscitation cycle by performing an earlier rhythm analysis. (February 2015) - Steinberg, Mikkel T.; Olsen, Jan-Aage; Brunborg, Cathrine; Persse, David; Sterz, Fritz; Lozano Jr, Michael; Brouwer, Marc A.; Westfall, Mark; Souders, Chris M.; van Grunsven, Pierre M.; Travis, David T.; Lerner, E. Brooke; et al.
Abstract: Background: Guidelines recommend 2 min of CPR after defibrillation attempts followed by ECG analysis during chest compression pause. This pause may reduce the likelihood of return of spontaneous circulation (ROSC) and survival. We have evaluated the possibility of analysing the rhythm earlier in the CPR cycle in an attempt to replace immediate pre-shock rhythm analysis. Methods and results: The randomized Circulation Improving Resuscitation Care (CIRC) trial included patients with out of hospital cardiac arrest of presumed cardiac aetiology. Defibrillator data were used to categorize ECG rhythms as shockable or non-shockable 1 min post-shock and immediately before next shock. ROSC was determined from end-tidal CO2, transthoracic impedance (TTI), and patient records. TTI was used to identify chest compressions. Artefact free ECGs were categorized during periods without chest compressions. Episodes without ECG or TTI data or with undeterminable ECG rhythm were excluded. Data were analyzed using descriptive statistics. Of 1657 patients who received 3409 analysable shocks, the rhythm was shockable in 1529 (44.9%) cases 1 min post-shock, 13 (0.9%) of which were no longer shockable immediately prior to next possible shock. Of these, three had converted to asystole, seven to PEA and three to ROSC. Conclusion: While a shockable rhythm 1 min post-shock was present also immediately before next possible defibrillation attempt in most cases, three patients had ROSC. Studies are needed to document if moving the pre-shock rhythm analysis will increase shocks delivered to organized rhythms, and if it will increase shock success and survival.